Avaliaç\~ao jurídica de mecanismos contratuais de compartilhamento de riscos de demanda para concess\~oes rodoviárias no Brasil - Levy Cunha Bravo; Edison Benedito da Silva Filho; Dianifer Leal Borges (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The purpose of this work is to present the main models for sharing demand risks in infrastructure concessions and discuss their advantages and limitations, as well as possible obstacles to their implementation in Brazil in light of the country's legal system and regulatory structure. We argue for the possibility of harmonizing contractual solutions such as revenue sharing and extending the concession period with the Brazilian regulatory framework. The recent success of the 5th round of federal highway concessions, which provide for the first time revenue sharing mechanisms to mitigate various risks, suggests that these solutions could contribute significantly to the expansion of private investments in the sector.
Keywords: R42; K12; 330; road infrastructure; risk sharing; administrative contracts